Investigating the Operating Performance of the Acquiring Firms in Chinese Mergers and Acquisitions - Xue, Yibei (2014)
Mergers and acquisitions have been regarded as one of a firm’s most important investment decisions. However, although there have been extensive empirical researches documenting the stock market return of firms around the announcement date, studies that examine the operating performance of either the acquirer or the target are very limited especially for Chinese M&A market. This study aims to investigate whether M&A in China create value for the operating performance for the listed acquiring firms. This study is based on 163 completed M&A transactions undertaken between January 1, 2000 and December 31, 2009, and conclusion can be drawn that the operating performance of the acquiring firms measured by three categories of indicators including accrual performance (return on assets, earnings per share), cash flow performance (cash flow return on total assets, cash flow return on sales), and growth opportunity (sales growth) consistently reveal significant improvements or no gains following a merger or an acquisition. Additionally, the cross-sectional regression analysis shows that the post-merger operating performance is significantly improved when the M&A is industry-related. Also, this study shows the acquirers have significantly better post-merger operating performance when the M&A is undertaken during the financial crisis period. Apart from that, none of the factors deal size, method of payment, and toehold investment is found to have significant impacts on the post-merger operating performance. Further, the conclusion drawn from five measures is still valid in the robustness test.